Circulating annexin A5 levels are associated with carotid intima-media thickness but not coronary plaque composition. (September 2017) - Burgmaier, Mathias; Reith, Sebastian; Schurgers, Leon; Kahles, Florian; Marx, Nikolaus; Reutelingsperger, Chris
Background: Annexin A5 (anxA5) is involved in processes which are crucial in atherogenesis. However, anxA5's relationship with atherosclerotic lesion extension and plaque composition in high-risk patients with type 2 diabetes remains unclear. Thus, we characterized the association between circulating anxA5 levels with atherosclerotic burden and coronary plaque composition in diabetes mellitus patients. Methods: Intima-media thickness was determined in 96 diabetes mellitus patients with stable coronary artery disease. Furthermore, intracoronary optical coherence tomography was performed in 106 lesions to determine plaque composition. Results: AnxA5 plasma levels of patients with intima-media thickening were higher (3.49 ± 2.19 ng/mL) compared to patients with normal intima-media thickness (2.24 ± 1.67 ng/mL, p = 0.002). Furthermore, anxA5 was associated with intima-media thickening on univariable [odds ratio = 1.445 (1.106–1.889), p = 0.007] and multivariable [odds ratio = 1.643 (1.166–2.314), p = 0.005] logistic regression analysis when adjusted for multiple cardiovascular risk factors and biomarkers. Furthermore, receiver operating characteristic analysis demonstrated that anxA5 predicted intima-media thickening with low–moderate diagnostic efficiency [area under the curve = 0.700 (0.592–0.808)]. In contrast, there was no association between anxA5 levels and coronary plaque composition as assessed by optical coherence tomography including the presence of lipid, calcified, fibrous plaque or the minimal thickness of the fibrous cap overlying the necrotic lipid core ( p = ns). Conclusion: Circulating anxA5 levels are associated with carotid intima-media thickness but not coronary plaque composition in high-risk patients with diabetes mellitus.